Upaya Mencegah Gangguan Muskuloskeletal di Perusahaan Bijih Plastik - Styllia Ariane Suyanto (Jurnal Titra, 2020)
The study was conducted at a plastic ore company. Problems obtained from observations and interviews, namely complaints in the skeletal muscle operator. The purpose of the research is to prevent the occurrence of complaints of musculoskeletal disorders. The Nordic Body Map questionnaire and disease history are distributed to determine complaints that are often experienced by operators. The Wilcoxon Signed Rank Test is used to compare the results of the Nordic Body Map questionnaire before and after work. Proposed improvements are made to each activity that affects skeletal muscle complaints that are often experienced by operators. The proposals given are moving raw material storage near the stage stairs, implementing work rotation, adding 1 operator, and applying manual lifting with the principle of ergonomics. In addition there is also the design of work facilities in the form of footrests and redesigning plastic ore storage tanks.